Establishing determinants of oxygen delivery and neuromuscular function at the heavy-to-severe intensity exercise threshold - Hammer, Shane Michael (Kansas State University, 2020)
Critical power/force (CP/CF) demarcates the boundary between the heavy- and severe-intensity exercise domains and is established as an important threshold for skeletal muscle metabolism, oxygen delivery, neuromuscular fatigue, and therefore exercise tolerance. Despite extensive study, the underlying mechanisms which precipitate the stark differences in physiological responses to exercise at intensities surrounding CP/CF remain unclear. The overall aim of this dissertation was to determine potential contraction-intensity dependent alterations in limb blood flow and microvascular oxygen delivery and investigate the effect of oxygen delivery limitations on neuromuscular function at the heavy-to-severe intensity exercise threshold (i.e., CP/CF). In our first investigation (Chapter 2), we demonstrated that limb blood flow and microvascular oxygen delivery responses during isometric handgrip exercise reached a physiological ceiling above, but not below, CF. Additionally, we determined that CF was the highest contraction-intensity at which this level of microvascular oxygen delivery could acutely sustain maximal-effort exercise. The second investigation (Chapter 3) demonstrated that limb vascular conductance is limited above CP and we provide evidence that limb blood flow limitations during severe-intensity exercise result, at least in part, from muscular contraction-induced vascular impedance. Importantly, this study utilized a dynamic large-muscle mass exercise model (supine leg cycling) to improve generalizability of our findings to activities of daily living. Utilizing complete blood flow occlusion and vascular reperfusion, the final investigation (Chapter 4) identified fatigue-induced restriction to central motor drive during maximal-effort handgrip exercise and established that CF represents an oxygen delivery-dependent balance between motor-unit activation and peripheral fatigue development. Collectively, contraction-intensity dependent limitations in oxygen delivery appear to exist during severe-intensity exercise such that progressive development of peripheral fatigue may result in restrictions to motor-unit activation. This dissertation presents novel findings that significantly contribute to our overall understanding of the physiological determinants of oxygen delivery, fatigue development, and exercise tolerance, which may be particularly relevant in patient populations that experience pathological limitations to oxygen delivery during exercise (e.g., heart failure and peripheral artery disease).
Keywords: Oxygen delivery; Blood flow; Muscle fatigue; Muscle activation; Exercise